RELIGIOSITY RELATED TO LIFE SATISFACTION, LOCUS OF CONTROL AND DEFENSE MECHANISMS - Mehrin Quazi Richi; Rumana Ferdousi Siddique (PEOPLE: International Journal of Social Sciences, 2025)
The proportion of non-religious individuals has been increasing rapidly over the last decade. Consequently, the interest in knowing whether there are any distinct psychological differences between those who believe in the creator and those who do not is also growing. Therefore, the present study aimed to investigate the association between religiosity and life satisfaction, locus of control, and defense mechanisms, and the differences between religious and non-religious individuals in terms of these factors. In this paper, data were collected from 90 non-religious individuals (atheists, and agnostics) by using snowball sampling, and 110 religious individuals (Muslim, Hindu, Buddhist, Christian) by using purposive sampling and choosing them according to their self-identified religions. It was found that religiosity is positively correlated with life satisfaction, external locus of control, and mature defense styles, and negatively correlated with neurotic defense styles. Moreover, religious participants scored significantly high on life satisfaction, external locus of control, and mature defense styles than non-religious individuals, and non-religious participants scored significantly high on neurotic defense styles than religious individuals. Though this paper can give an outlook of the answers to our present questions, but further research should be done, including the data of the degree of religious involvement of religious individuals for a clear outcome.